Diseño y construcción de un sistema automático cnc de 4 ejes para corte de tubo redondo, cuadrado y rectangular por plasma con diseño en 2d y extensión dxf en la empresa “Cnc Ecuador.ec”, ubicada en la parroquia San Buenaventura de la ciudad de Latacunga provincia de Cotopaxi - Galarza Lasluisa, Luis Miguel (2022)
The current project has as aim to design and build a CNC machine tool for cutting square, round and rectangular tubes by plasma, since metalworking micro-enterprises have the making cuts difficulty, whose require linear, angular dimensions and perforations, which were determined its dimensions and were defined all the mechanical, electronic and electrical components used for its operation, and it was made the My Plasm System control card configuration, automatically to generate instructions into G codes from CAD files into 2D DXF format. This document, as a first part was briefly reviewed some related topics with project, whose involve industrial robotics and CNC systems.